Molecular cloning, expression and characterization of a serine proteinase from Japanese edible mushroom, Grifola frondosa: solving the structure - function anomaly of a reported aminopeptidase - Islam, Mohammed M. (Electronic Journal of Biotechnology, 2008)
The N-terminal amino acid sequence of an aminopeptidase from Japanese edible mushroom, Grifola frondosa, was reported to have high similarity with that of a serine proteinase from basidiomycete, Agaricus bisporous (Nishiwaki and Hayashi, 2001). The full-length cDNA and the corresponding genomic DNA of the enzyme were cloned, based on the reported N-terminal amino acid sequence. The predicted open reading frame (ORF) of the cloned cDNA, encoding a product of 379 amino acids, was expressed in E. coli using pET expression vector. The expressed pro-enzyme (40 kDa) underwent autolysis to produce the mature protein (30 kDa) and a pro-peptide (10 kDa). The mature protein and the pro-peptide remained tightly bound to each other and could not be separated by Ni-NTA metal affinity chromatography or Q-Sepharose ion-exchange chromatography. The enzyme was inactive in the bound form. Upon treatment with subtilisin, the bound pro-peptide was further hydrolyzed and a high serine proteinase activity was recovered. No aminopeptidase activity was detected at any stage of the protein processing. These results clearly indicated that the N-terminal amino acid sequence and the function of the reported aminopeptidase were not derived from the same protein entity and hence caused the structure-function anomaly.